PELATIHAN PEMASARAN DIGITAL BERBASIS MEDIA SOSIAL UNTUK PENGUATAN KAPASITAS KELOMPOK TANI SEHASE I - Puspita, Desi; Syahri, Riduan; Putrawansyah, Ferry (FORDICATE, 2025)
This community service activity aims to increase the capacity of the Sehase 1 Farmer Group in terms of marketing agricultural products through the use of social media. In today's digital era, social media is an effective and efficient means to promote products widely without geographical limitations. The methods used in this activity include training, mentoring, and evaluation of the use of social media platforms such as Instagram, Facebook, and Tiktok. The indicator of the success of the assistance activity for processing chilies into chili powder is by measuring before (pre-test) and after (post-test) the extension with the level of knowledge and skills of participants in terms of making and benefits of chili powder and the quality of chilies in the long term. The results obtained were a high increase in farmer knowledge and skills with a percentage level of 98.83% in the high category. The results of the activity showed an increase in the knowledge and skills of farmer group members in creating digital content and managing social media accounts professionally